Dikaiosyne – sprawiedliwość. Genealogia pojęcia - Juchacz, Piotr W. (Filozofia Publiczna i Edukacja Demokratyczna, 2012)
The concept of justice takes a central position in practical philosophy from the birth of philosophical reflection in the ancient Greece to contemporary discussions in political, social, and moral philosophy. This article presents a genealogy and development of the Greek concept of dikaiosyne (δικαιοσύνη). It starts with the first poetical appearances of a term dike (δίκη) in Homer’s poetry, continues with the analysis through its more sophisticated application by Hesiod, and finally it reaches the pivotal philosophical transformations of dike into dikaiosyne in The Histories of Herodotus.